Learning Based On Information Technology and Learning Strategy Communication in Facing Industrial Revolution Era 4.0 - Warih Bimayu; Nopriadi Nopriadi (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2019)
The educational world in Indonesia experiences a phenomenon in the face of the era of industrial revolution 4.0, this can have a significant impact on the world of education. Many scientists, experts, organizations, educational institutions, universities make strategies in facing the era of industrial revolution 4.0. One of them conducted by the Federation of Information and Communication Technology Teachers) held a workshop in Jakarta, 6-7 October 2018 themed "Dynamics of ICT / Informatics Learning Policies in the Age of Industrial Revolution 4.0 and Increased Competence of ICT/Informatics Teachers on 21st Century Learning". This study aims to determine the ICT-based learning strategies applied at Public Senior Scondary School 1 Sungai Rotan in the face of the Industrial Revolution 4.0 era. Sources of data obtained by researchers from teachers as the object of research at Public Senior Scondary School 1 Sungai Rotan and obtained from the latest information in the world of education related to the era of industrial revolution 4.0. The data of this study were collected using the method of documentation and direct interviews with subject teachers. The findings of the data obtained were then analyzed by researchers that at Public Senior Scondary School 1 Sungai Rotan had a reliable strategy in facing the era of industrial revolution 4.0 because it was proven in every learning that all teachers had applied ICT-based learning, the use of laptops (computers) and the internet was the wrong one that should not be ignored which is integrated in the curriculum.